Unveiling the Creative Teacher’s Secret: A Systematic Review of Learning Variations for Active Classrooms - Arifin, Samsul; Pratama, Moh Beni; Jaini; Agustiawati, Dwi; Amelya, Zahrina; Nashriya, Fatima Shalha (Indonesian Journal of Learning and Instructional Innovation, 2025)
The changing times require teachers to be more creative in creating learning that is not monotonous in order to increase student motivation and participation. This research aims to explain the meaning of learning variation and its role in building an active and interesting classroom atmosphere, identify variation skills such as teaching style, media, and interaction, and analyze the principles of their use. This research uses a qualitative approach with a library research method, where data is collected through document analysis from relevant books and journals. This research synthesizes contemporary pedagogical innovations, including AI integration and play-based strategies, to provide a comprehensive framework for creative teaching in the post-pandemic era. The results show that learning variations have a significant influence in overcoming learning boredom, improving understanding, and adjusting the learning process to students' diverse learning styles. Teachers who are able to creatively combine methods, media, and interactions prove more successful in creating a dynamic and meaningful learning atmosphere. In conclusion, learning variation is not only a teaching strategy, but also the key to creating a classroom that is inclusive, adaptive and supports the development of 21st century skills in students.